PERBANDINGAN AKURASI RASIO CASH FLOW DENGAN ECONOMIC VALUE ADDED UNTUK MEMPREDIKSI KINERJA KEUANGAN PERUSAHAAN - Nekhasius Agus Sunarjanto (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This research aims to determine whether Economic Value Added (EVA) and cash flow ratios can differentiatebetween healthy-performing companies with unhealthy performing companies in manufacturing companieslisted in the Indonesia Stock Exchange. The results of this study indicates that EVA and cash flow ratios candifferentiate significantly between companies with sound financial performance that is not healthy atmanufacturing companies listed in the Stock Exchange. This can be seen from Wilk's Lamda value of 0.901 asindicated by the Chi-square value of 37.306 and has a significance level of alpha 0000 below 5%. It means thatthe model is statistically significant. Hence, it is concluded that the average performance of a healthy orunhealthy performing companies and this model can be utilized to predict the company's financial performance.Key words : financial performance, ratio cash flow, Economic Value Added